(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Flash burns are an exogenous burn, and they’re a variant of flame burns. Usually, flame burns produce high heat for a long time, until the body is charred or complete combustion. Whereas flash burns produce intense heat in a short period of time and affect superficial layers or clothing’s. Though flash burns produce first-degree burns in most cases, with a few exceptions: explosions of huge intensity, high-tension electricity, lightning strikes, and bomb blasts Without a blast, flash burns are the rarest entity, but it is very much possible when domestic sources produce a smaller quantity of flammable liquids, such as gasoline or petrochemical products, at the scene of a crime, whether accidental or intentional. In this case series, five cases of unburst flash burn fatalities were analysed with medicolegal investigation aspects. Flash burns occur in the blink of an eye with an initial sudden ignition, are mostly accidental, and produce superficial, partial burns. The most challenging task for forensic medicine experts during medical legal investigations of burn fatalities is establishing the identity of the victim. But the level of difficulty will be lower with incomplete, superficial burns like flash burns. Accidental and suicidal fatalities with fire are preventable with necessary corrective actions, and this article is a stepping stone thrown at us to bridge the gap.